Distribution and physical–biological controls of dimethylsulfide in the western tropical Indian Ocean during winter monsoon - Liang, Shi-Mei; Zhai, Xing; Li, Cheng-Xuan; Xin, Ming; Sun, Ping; Liu, Xuan-Li; Liu, Lin; Wang, Bao-Dong (Frontiers in Marine Science, 2023)
New field observation on distribution, turnover, and sea–air flux of three dimethylated sulfur compounds (dimethylsulfide (DMS), dimethylsulfoniopropionate, and dimethylsulfoxide) in the western tropical Indian Ocean (WTIO; 4°N–10°S, 61°–65°E) were conducted under the major Global Change and Air–Sea Interaction Program during the 2021/2022 Northeast Monsoon (December 21, 2021 to January 11, 2022). Significantly high surface concentrations of DMS were identified in the region of the Seychelles–Chagos Thermocline Ridge (SCTR; 5°–10°S). This occurred because the shallow thermocline/nitracline and associated upwelling fueled biological production of DMS in the subsurface, which was brought to the surface through vertical mixing. The calculated sea–air DMS flux was also significantly strong in the SCTR region during the Northeast Monsoon owing to combination of high wind speed and high surface concentration of DMS. This finding is similar to results obtained previously during the Southwest Monsoon, suggesting that the SCTR region is an area of active DMS emission during both the Northeast Monsoon and the Southwest Monsoon. Microbial consumption was the dominant pathway of DMS removal, accounting for 74.4% of the total, whereas the processes of photolysis (17.7%) and ventilation (7.9%) were less important. Future work should be undertaken in the WTIO to establish how DMS emission is linked to aerosol properties and climate change.